2016
DOI: 10.1161/jaha.115.002931
|View full text |Cite
|
Sign up to set email alerts
|

Regional Implementation of a Pediatric Cardiology Syncope Algorithm Using Standardized Clinical Assessment and Management Plans (SCAMPS) Methodology

Abstract: BackgroundPediatric syncope is common. Cardiac causes are rarely found. We describe and assess a pragmatic approach to these patients first seen by a pediatric cardiologist in the New England region, using Standardized Clinical Assessment and Management Plans (SCAMPs).Methods and ResultsAmbulatory patients aged 7 to 21 years initially seen for syncope at participating New England Congenital Cardiology Association practices over a 2.5‐year period were evaluated using a SCAMP. Findings were iteratively analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 34 publications
0
24
0
3
Order By: Relevance
“…Coincident with this EBG, the Department of Cardiology at Boston Children’s Hospital also examined their ambulatory practices in the evaluation of syncope. 20 The division chief’s annual evaluation of physician performance, including rotating metrics of adherence to a single guideline as a marker of evidence-based practices, likely promotes adherence to the guidelines. Lastly, escalating national discussion on cost containment in healthcare may have impacted clinical practices.…”
Section: Discussionmentioning
confidence: 99%
“…Coincident with this EBG, the Department of Cardiology at Boston Children’s Hospital also examined their ambulatory practices in the evaluation of syncope. 20 The division chief’s annual evaluation of physician performance, including rotating metrics of adherence to a single guideline as a marker of evidence-based practices, likely promotes adherence to the guidelines. Lastly, escalating national discussion on cost containment in healthcare may have impacted clinical practices.…”
Section: Discussionmentioning
confidence: 99%
“…An important limitation of the current study is the use of a single center design, limiting the generalizability of the results to other institutions and patient populations. Although we have shown that SCAMPs can be deployed across multiple institutions in a network, each center will need to validate the impact of a SCAMP on their practice. The costs required to create, execute, and analyze the ASO SCAMP were not measured.…”
Section: Limitationsmentioning
confidence: 99%
“…1 and Table 1). Regional implementation of pediatric SCAMPs for evaluation of chest pain and syncope in children and adolescents has been successful and well-received by both providers and patients [38,39]. The first hurdle facing any care pathway is achieving physician buy-in, which can be partially assessed by measuring adherence and resultant practice variation.…”
Section: Standardized Clinical and Management Pathwaysmentioning
confidence: 99%
“…Resource utilization also significantly decreased for a number of diagnostic testing modalities commonly used in the evaluation of chest pain. In the pre-SCAMP cohort, nearly 30 % of patients underwent exercise stress testing, despite a lack of established clinical utility demonstrated in several studies [38][39][40][41]. In the SCAMP period, utilization of this test decreased to ∼3 % of patients.…”
Section: Standardized Clinical and Management Pathwaysmentioning
confidence: 99%